A double‐blind randomized controlled trial of oxytocin nasal spray in Prader Willi syndrome. Issue 9 (30th June 2014) - Einfeld, Stewart L.; Smith, Ellie; McGregor, Iain S.; Steinbeck, Kate; Taffe, John; Rice, Lauren J.; Horstead, Siân K.; Rogers, Naomi; Hodge, M. Antoinette; Guastella, Adam J.
<x xml:space="preserve">Abstract</x> Individuals with Prader–Willi syndrome (PWS) have a significant reduction in the number of oxytocin‐producing neurons (42%) in the hypothalamic paraventricular nucleus. A number of animal studies and observations of humans show that lesions in this region can produce PWS‐like symptoms. Given the evidence for potential oxytocin deficiency, we tested the effects of a course of intranasal oxytocin on PWS symptoms. Thirty individuals with PWS aged 12–30 years participated in an 18‐week randomized double‐blind placebo‐controlled crossover trial. Participants received 8 weeks of oxytocin and 8 weeks of placebo with a minimum 2‐week washout period. The first 11 participants received the following oxytocin doses: 24 IU (twice daily) B.I.D for participants 16 years and over and 18 IU B.I.D for participants 13–15 years. The dose was increased for the remaining 18 participants to 40 IU B.I.D for participants 16 years and over and 32 IU B.I.D for 13–15 years. Measures used to assess changes were standardized well‐accepted measures, including the Developmental Behavior Checklist—Monitor, Parent, Teacher, and Adult; The Yale‐Brown Obsessive Compulsive Scale; The Dykens Hyperphagia questionnaire; Reading The Mind in the Eyes Test; Epworth Sleepiness Scale and the Movie Stills. Oxytocin had little impact on any measure. The only significant difference found between the baseline, oxytocin, and placebo measures was an increase in temper outbursts (P = 0.023) with higher dose oxytocin. The lack of effect of oxytocin nasal spray may reflect the importance of endogenous release of oxytocin in response to exogenous oxytocin. © 2014 Wiley Periodicals, Inc.